(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The article provides a scientific analysis of improving the corporate governance system based on innovative approaches and integrating it with sustainable development strategies. In the modern economic environment, the effective use of innovative management methods is identified as a key factor in ensuring the competitiveness of companies, protecting shareholder interests, and creating long-term value. The study highlights the main directions for enhancing the effectiveness of corporate governance, including strategic innovations, mechanisms that ensure openness and transparency, constructive dialogue with stakeholders, and factors that support socio-economic sustainability. Moreover, the positive influence of innovative approaches on shaping corporate culture and strategic decision-making processes is examined, demonstrating their theoretical and practical significance in promoting the long-term sustainable development of companies.